2018
DOI: 10.1002/pip.3063
|View full text |Cite
|
Sign up to set email alerts
|

Resilient and reproducible processing for CZTSe solar cells in the range of 10%

Abstract: In this paper, we present our route to fabricate Cu2ZnSnSe4 (CZTSe) thin films, which allows to achieve reproducible processing of kesterite absorber, that leads to efficiencies in the range of 10%. The article mainly focuses on the annealing process and demonstrates that controlling of the reactor pressure for selenization can be reliably used to tune the losses of volatile constituents in the absorber, enabling adjustments on the properties of the film and solar cell. The findings reveal a noteworthy resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…7,8 An appropriate conguration of alloy precursors during kesterite processing is also known to improve the thin lm homogeneity; 9,10 moreover, using this alloy structure, reproducible and resilient kesterite absorber processing with device efficiencies above 11% can be achieved. 11,12 In this study, we report the optimization of the selenium amount during the annealing process for precursor stacks with Cu-Sn alloy layers. We have discussed the crucial impact of excess Se on the material properties and ne-tuning of the Se amount for improving the opto-electronic properties of the Cu 2 ZnSnSe 4 (CZTSe) material that nally results in the enhanced performance of solar cell devices.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 An appropriate conguration of alloy precursors during kesterite processing is also known to improve the thin lm homogeneity; 9,10 moreover, using this alloy structure, reproducible and resilient kesterite absorber processing with device efficiencies above 11% can be achieved. 11,12 In this study, we report the optimization of the selenium amount during the annealing process for precursor stacks with Cu-Sn alloy layers. We have discussed the crucial impact of excess Se on the material properties and ne-tuning of the Se amount for improving the opto-electronic properties of the Cu 2 ZnSnSe 4 (CZTSe) material that nally results in the enhanced performance of solar cell devices.…”
Section: Introductionmentioning
confidence: 99%
“…CZT(S,Se) growth processes based on the sputtering technique can be classified depending on the target(s) type(s) and on the deposition sequence. Either pure metallic (Cu, Zn, Sn), metallic alloys (Cu-Sn, Zn-Sn) [55][56][57][58][59] or chalcogen-containing (binary chalcogenides ZnS(e), SnS(e), SnS(e) 2 or Cu x S(e)) [5,[60][61][62] targets and their combinations [36] have been used for the synthesis of kesterites as absorber layers. Concerning the deposition sequence, processes based on sequential [5,6,9,56] or co-sputtering of different targets [61,62], leading respectively to stacked-layer or homogeneously-mixed precursors, have been extensively investigated.…”
Section: Sequential Sputtering/co-sputteringmentioning
confidence: 99%
“…Besides the progresses related to improvements in solar cell technology such as optimization of new buffer [23] and passivation layers [63], the efficiency progress is also due to the elucidation and improved control of the reaction pathways during the absorber formation. It has been shown that a route involving Cu 2 SnX 3 (X=S or Se) and ZnX is preferred over reaction paths involving binary compounds (Cu 2 X, SnX 2 and ZnX) [64,36], since loss of SnS(Se) volatile species during the annealing treatment can be suppressed.…”
Section: Sequential Sputtering/co-sputteringmentioning
confidence: 99%
See 2 more Smart Citations